Lessons from London: a contemporary examination of the factors affecting attrition among rape complaints. Issue 1 (2nd January 2022) - Murphy, Anthony; Hine, Ben; Yesberg, Julia A.; Wunsch, Daniela; Charleton, Barry
ABSTRACT: Severe levels of attrition in rape cases within the criminal justice system are widely recognised. Previous reviews (e.g. Hohl & Stanko, 2015 . Complaints of rape and the criminal justice system: Fresh evidence on the attrition problem in England and Wales. European Journal of Criminology, 12 (3), 324–341) have provided information on the general profile of cases, their outcomes, and the relationship between the two, in attempts to understand these patterns. However, recent changes to the landscape of rape investigation (e.g. the impact of technology) justify a more contemporary assessment. The present study coded 446 cases of rape reported in London in April 2016, on a variety of victim, suspect, offence, and procedural characteristics, as well as case outcomes. We conducted descriptive analyses of case profiles and inferential examinations of the relationship between case characteristics and outcomes. Findings suggest the profile of victims, suspects, and the context of offences has remained mostly similar, with some noticeable changes (e.g. a larger array of victim vulnerabilities). Moreover, several existing, exacerbated, as well as novel procedural challenges present (e.g. delay due to workload, third party materials). Additionally, many rape-myth related case factors no longer predict case outcomes and officers instead may now engage in greater 'downstream' orientation, and anticipation of case uptake, when evaluating cases. Recommendations for policy and practice are discussed.